"Purchased in Hong Kong": Is Hong Kong the Best Place to Buy Stolen or Looted Antiquities?. Issue 4 (14th December 2017) - Gallagher, Steven
Abstract: The looting of antiquities from archaeological sites has received widespread coverage in the media. Concerns about the loss of heritage have resulted in international multilateral and bilateral agreements intended to prevent the illicit trade in looted antiquities. China has suffered from the looting of its archaeological sites for centuries, but the problem has been exacerbated in recent years because of the increased demand for Chinese antiquities and the consequent sharp increase in market prices. China has requested international assistance to combat the illicit trade in its heritage. It is strange therefore that one of China's special administrative regions—Hong Kong—also one of the world's major art markets, retains a "legal absurdity, " 1 which may protect the buyer of stolen or looted goods from claims for the return of stolen items. This statutory provision may result in the bizarre outcome that goods stolen from a museum or looted from an archaeological site and then purchased from a shop or market in Hong Kong may be protected from claims for their return; this protection may apply even if the loser is the Chinese state.